2017
DOI: 10.3390/su9101859
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Ecological Compensation Standards for Fallow Heavy Metal-Polluted Farmland in China Based on Farmer Willingness to Accept

Abstract: Abstract:In the context of China's trial fallow policy; the heavy metal pollution of farmland is addressed via field surveys in Hunan Province, where the fallow policy has been implemented, and in Jiangxi Province, where it has not been implemented. We measured and analyzed willingness to accept (WTA) using the contingent valuation method (CVM). The conclusions of this study are as follows: (1) Farmer awareness of heavy metal pollution and pollution sources is higher in Jiangxi Province than in Hunan Province;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 32 publications
0
23
0
Order By: Relevance
“…The planting area accounts for more than 60% of the province. However, it is common for farmers to apply excessive fertilization and poorly planned irrigation in the management process, and the soil environmental problems caused by these methods are substantial [6,7]. In the process of the growth and development of crops, the absorption and utilization of N nutrients are limited.…”
Section: Introductionmentioning
confidence: 99%
“…The planting area accounts for more than 60% of the province. However, it is common for farmers to apply excessive fertilization and poorly planned irrigation in the management process, and the soil environmental problems caused by these methods are substantial [6,7]. In the process of the growth and development of crops, the absorption and utilization of N nutrients are limited.…”
Section: Introductionmentioning
confidence: 99%
“…The possible reason is that the change of social benefits caused by FRP is not evenly distributed between urban and rural samples. Rural residents are more likely to take the risks caused by land retirement than urban residents [48]. Urban residents have higher WTPs for levels of vegetation type attribute, but lower WTPs for levels of priority zone attribute than that of the urban residents.…”
Section: Welfare Analysismentioning
confidence: 95%
“…Even if the farmers' awareness of heavy metal pollution and pollution sources is higher in Jiangxi province than in Hunan province, the WTA of farmers in Hunan Province is a little higher at 934.39 (yuan/mu), than the 839.34 (yuan/mu) in Jiangxi Province. It implies that the factors affecting the WTA of farmers in Hunan Province are much diverse due to the compensation incentives [9]. This comparison showed that too strong intervention by the policy regime may result in moral hazard among farmers.…”
Section: Feasibility Issues Of the Regional Cooperationmentioning
confidence: 99%
“…In the early 2010s, most of the research focused on the regional or provincial difference, while during the middle of the 2010s, major focus moved to the city or county level. Xie et al analyzed the comparative advantages of the environmental incentives on the heavy metal-polluted farmland in China, based on farmers' willingness to accept (WTA) and its compensation for the land [9]. They compared the two provinces of Hunan, where the fallow policy has been implemented, and Jiangxi, where it has not been implemented yet.…”
Section: Feasibility Issues Of the Regional Cooperationmentioning
confidence: 99%